Effects of age on intake, growth, nutrient utilization and carcass characteristics of castrated native sheep (Bangladesh Veterinarian, 2011)
Twenty four castrated native sheep were grouped (six/group) into four: T1 >3 to ≤ 6; T2 > 6 to ≤ 9; T3 >9 to ≤12 and T4 >12 to ≤ 15 months. Through out the 63 days of experimental period, animals were offered ad libitum urea (3%), molasses (15%) and straw (82%) as a basal diet with concentrate mixture [14% crude protein (CP) & 11.5 MJ metabolizing energy (ME) per kg Dry Matter (DM)] @ 1% of live weight. Five days metabolic trial was conducted towards the end of the feeding trial. Besides, fortnightly live weight change, daily nutrient intake, carcass yield and carcass characteristics were studied. Daily weight gain decreased (P